Perancangan Sistem Pencatatan Laporan Keuangan Dan Perpajakan Sederhana Berbasis Excel Untuk Efisiensi Biaya Produksi Pada UMKM Pempek Edi - Sonia Septiana (Journal of Applied Accounting And Business, 2026)
Micro, Small, and Medium Enterprises (UMKM) play a significant role in Indonesia’s economy; however, many still face challenges in financial management and tax compliance. UMKM Pempek Edi in Jambi City is a small culinary business that conducts daily production and sales activities without a structured financial recording system. This condition makes it difficult to control production costs, prepare financial statements, and calculate tax obligations accurately. This study aims to analyze the existing financial and taxation practices and to design a simple Microsoft Excel–based financial and tax recording system to support production cost efficiency. The research employs a descriptive qualitative method using interviews, observations, and documentation as data collection techniques. The designed system includes daily transaction recording, production cost calculation, preparation of financial statements in accordance with SAK EMKM, and a simulation of the 0.5% Final Income Tax calculation based on gross turnover. The results indicate that the Excel-based system improves the orderliness of financial records, enhances production cost control, and facilitates MSME owners’ understanding of tax obligations.